2021
DOI: 10.1093/humrep/deab135
|View full text |Cite
|
Sign up to set email alerts
|

Hypo-glycosylated hFSH drives ovarian follicular development more efficiently than fully-glycosylated hFSH: enhanced transcription and PI3K and MAPK signaling

Abstract: STUDY QUESTION Does hypo-glycosylated human recombinant FSH (hFSH18/21) have greater in vivo bioactivity that drives follicle development in vivo compared to fully-glycosylated human recombinant FSH (hFSH24)? SUMMARY ANSWER Compared with fully-glycosylated hFSH, hypo-glycosylated hFSH has greater bioactivity, enabling greater follicular health and growth in vivo, with enhanced transcriptional activity, greater activation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 64 publications
5
20
0
Order By: Relevance
“…As FSH24 increases with age, with potential to promote follicle atresia, it may in part contribute to the accelerated follicle depletion observed with aging ( 51 , 52 ). Furthermore, the differences in FSH target gene expression (steroidogenic enzymes) are in concordance with previous in vitro studies in cultured human GCs ( 53 ) and in vivo studies ( 41 , 43 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As FSH24 increases with age, with potential to promote follicle atresia, it may in part contribute to the accelerated follicle depletion observed with aging ( 51 , 52 ). Furthermore, the differences in FSH target gene expression (steroidogenic enzymes) are in concordance with previous in vitro studies in cultured human GCs ( 53 ) and in vivo studies ( 41 , 43 ).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies investigating the effects of partially glycosylated FSH21/18 and fully glycosylated FSH24 glycoform preparations have predominately utilized acute measurements in heterologous cell lines expressing FSHR, isolated GCs, and in vivo and ex vivo ovaries ( 43 , 41 ) This study provides important next steps in understanding the effects of FSH glycoforms on longer-term pre-antral follicle cultures, analyzing the effects of FSH glycoforms when follicles become sensitive to FSH. Moreover, this study presents the first ratiometric analysis of FSH21/18:FSH24, mimicking the reported aging-dependent changes and showing titratable effectiveness of FSH21/18 in promoting follicle growth and survival with increasing in FSH24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional analysis has shown that this difference in glycosylation pattern results in modulation of binding to the FSHR (14) and the amplitude of the canonical FSHR signaling pathway, the Gas/cAMP/PKA signaling, with FSH21/18 displaying faster binding kinetics and more potent activation of Gas signaling (15)(16)(17). Recent studies suggest that FSH glycoforms may display distinct signaling profiles, or signal bias (18) in activation of AKT (19,20), b-arrestin (17) and calcium signaling (17,21). Important functional differences have also been observed, with differences in ovarian and testicular gene expression in mice injected with either FSH21/18 or FSH24 (19).…”
Section: Introductionmentioning
confidence: 99%
“…This complexity in signal profiles offers the ability of GPCRs such as FSHR to exhibit bias in their signaling, where one, or more, pathways, may be preferentially activated over others. Such bias has been well documented and may be both ligand and cell/ system specific (30)(31)(32)(33)(34). The pluri-dimensional signaling capacity of FSHR offers a mechanism underlying the multiple and dynamic functions of FSH/FSHR in target cells including proliferation, steroidogenesis, apoptosis and differentiation (31,(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%